2002
DOI: 10.3109/s101650200025
|View full text |Cite
|
Sign up to set email alerts
|

Renal involvement in rheumatoid arthritis: analysis of renal biopsy specimens from 100 patients

Abstract: We analyzed renal biopsy specimens from 100 patients to evaluate the characteristics of renal involvement in patients with rheumatoid arthritis (RA). Membranous nephropathy (MN) was the most common renal histological pattern (31%). Mesangial proliferative glomerulonephritis (GN) was found in 21% of cases (IgA nephropathy 12%, non-IgA GN 9%), minor changes in 17%, renal amyloidosis in 11%, interstitial nephritis in 9%, sclerotic GN in 4%, and crescentic GN in 2%. MN was relatively more frequent in men than in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 14 publications
1
31
0
4
Order By: Relevance
“…IgA nephropathy is the prototype of MePGN. Secondary MePGN is documented in a variety of disorders, such as systemic lupus erythematosus, Henoch-Schönlein purpura, rheumatoid arthritis, and vasculitic syndromes (27)(28)(29). Therapeutic response to corticosteroid and colchicine has been reported in a few patients with MePGN who harbored heterozygous MEFV gene mutations (3,4,24,26).…”
Section: Discussionmentioning
confidence: 99%
“…IgA nephropathy is the prototype of MePGN. Secondary MePGN is documented in a variety of disorders, such as systemic lupus erythematosus, Henoch-Schönlein purpura, rheumatoid arthritis, and vasculitic syndromes (27)(28)(29). Therapeutic response to corticosteroid and colchicine has been reported in a few patients with MePGN who harbored heterozygous MEFV gene mutations (3,4,24,26).…”
Section: Discussionmentioning
confidence: 99%
“…Makino et al reported the results of renal biopsies in 100 patients with RA. These patients had a great heterogeneity of renal lesions, and the most frequent finding was membranous nephropathy (n = 31) and only 6 of these cases were considered not related to DMARDs (3). Renal amyloidosis was detected in 11 patients and only 2 patients had crescentic GN.…”
Section: Discussionmentioning
confidence: 99%
“…Another relevant aspect in this case is the absence of amyloid deposits in kidney, even after, approximately, 30 years since the diagnosis of RA. The incidence of renal amyloidosis in patients with RA varies from 11% to 30%(1,3) and is associated with poor renal outcome(3). …”
Section: Discussionmentioning
confidence: 99%
“…Renal dysfunction and urinary abnormalities, which are usually related to drug toxicity, secondary amyloidosis, or those which overlap with other autoimmune conditions, are frequently observed in patients with rheumatoid arthritis (1). Membranous nephropathy is well-known to occur in rheumatoid arthritis patients treated with gold salt, Dpenicillamine or bucillamine (1)(2)(3). Here, we describe a patient with short-duration rheumatoid arthritis who presented with membranous nephropathy associated with the relatively selective cyclooxygenase-2 inhibitor, etodolac (4).…”
Section: Introductionmentioning
confidence: 99%